MEANING WITHIN THE MOVIE POSTERS OF “DESPICABLE ME” MOVIE SERIES: A SEMIOTIC ANALYSIS - Cahyani, Ni Made Rosita; Maharani Santika, I Dewa Ayu Devi; Ariyaningsih, Ni Nyoman Deni (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2022)
This study aims to find out the behind meaning or messages of the semiotic signs that were found in the four movie posters of Despicable Me. The data of this study is downloaded from https://id.pinterest.com, an online application (that can be downloaded in the play store) that provide services for people to exploring, searching or sharing images. To discover the behind messages of the semiotic signs in the movie posters, this study uses the theory of meaning by Barthes (1977) and the theory of color meaning by Wierzbicka (1996) as a supporting theory. The method used to analyze the data on this research is the qualitative research method. In the end, the result of this study reveals, all the behind messages of the semiotic sign found in the four posters are represent the movie by giving more context about the story, the theme, and the character in the movie.